Using Duolingo Application In Learning Vocabulary: A Descriptive Qualitative Study At The Fifth Grade Of An Elementary School In Sumedang - Rahma Sakina; Riyanti Sri Astuti (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2024)
The use of technology in education, particularly in language learning, has become increasingly prevalent. Among the numerous language learning applications available, Duolingo has gained significant popularity. The research titled "Using Duolingo Application in Learning Vocabulary" aims to analyze students' perceptions and to investigate the benefits and challenges that students and teachers find using the Duolingo application in teaching and learning vocabulary. This research was conducted in the fifth grade of an elementary school in Sumedang and data were obtained from 18 students namely 10 females and 8 males. The research was conducted using a descriptive qualitative method, which used observation, questionnaires, and interviews as instruments. The findings show that students' perceptions of the use of the Duolingo application in vocabulary learning received a positive responses. The benefits of Duolingo were also identified (1) students can feel that motivation to learn English by using the Duolingo application, (2) students can learn new vocabulary after using the Duolingo application, (3) students find it easy to memorize and remember new vocabulary, and (4) students can use vocabulary in daily conversations. However, this research also revealed several challenges, such as a mismatch between the material taught at school and that in the Duolingo application, as well as limited access to technology such as laptops and speakers when used in class. The implications of this research show that, with appropriate adjustments and support, Duolingo can be an effective tool in improving students' English skills, especially vocabulary. Moreover, it demonstrates the need for improved technological infrastructure and alignment of learning materials.